Pembuatan Sistem Informasi Pembayaran Biaya Kos Berbasis Web Di Asrama Natuna Kota Pekanbaru Riau - Hubbairah, Qhory; Dahliyusmanto, Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Natuna Dormitory is a dormitory inhabited by students who came from Natuna Regency. Natuna hostel is located on Jalan Bangun Karya in Pekanbaru-Riau Province. The payment system at Natuna Dormitory is still manual, which is using a notebook, so there is often a writing error in payment, if using a risk book that will lose a notebook so that payment data will be lost, for this reason an information system is made namely the Payment Information System Web Based Board Fee. On this system the programming language used in the design of this system is, Hypertext Preprocessor(PHP), Hypertext Markup Language(HTML), JavaScript(JS), My Structured Query Language(MySQL). Waterfall Method used in this research is a systematic and sequential model of information system development. Waterfall Method has stages that are carried out sequentially. Results of this research is a Payment Information System that can facilitate administrators in the payment process, a payment receipt for every tenant, monthly report for owner of Natuna Dormitory. There is also another feature system such us SMS Gateway for sending SMS notifications to every tenant 3 days before payment, payment due and late payment. In this system, payment is made by entering the tenant's name and the number of months to be paid, then printing a payment receipt to be provided to the tenant. On the other side, payment record will be sent into a monthly report of the owner of Natuna Dormitory. Keywords: Information Systems, Payment, Programming Languages, Waterfall Methods.